RURAL INSURANCE AND ECONOMIC PROMOTION OF FAMILY AGRIBUSINESS (CIPEEX, 2025)
Knowing that there are various tools that can be used as mechanisms capable of promoting the economy of rural communities, it is clear to discuss whether the securitization of rural activities, or rather, of agribusiness, would have this power.Hence the reason for the study to point out the impact of rural insurance on the economic activity of rural producers and their communities in Brazil, believing that the contracting of this type of insurance, by reducing uncertainty and the impact of large losses, encourages new investments generating development. The work's guiding hypothesis, considering that the creation of a network of policyholders would strengthen the economy of rural communities as a result of mutualism.